Carbon emissions from selective logging in the southern Yucatan Peninsula, Mexico - Armenta-Montero, Samaria; Ellis, Edward A.; Ellis, Peter W.; Manson, Robert Hunter; Lopez-Binnqüist, Citlalli; Villaseñor Pérez, Juan Alberto (Instituto de Ecología, A.C., 2020)
Tropical forests contain approximately 40% of the carbon accumulated in terrestrial biomass. However, the loss and degradation of forests worldwide liberates this carbon and contributes 11% of total global emissions. Forest degradation is an increasing source of carbon emissions, contributing 25% in tropical forest environments; and selective logging is among the principal causes.  The central objective of this study was to evaluate biomass impacts and committed carbon emissions from selective logging in two forestry communities (ejidos with common forest use and rights) in the southern Yucatan Peninsula, Mexico. We compared emissions performance from logging operations in both ejidos, one of them certified as sustainably managed by the Forest Stewardship Council (FSC). The species of roundwood extracted as well as the number of impacted trees from harvesting were recorded and the type of collateral damage from felling, skidding, and transport of timber was quantified. Biomass of harvested timber and impacted vegetation was estimated to calculate carbon emissions using allometric equations. Results indicated that selective logging generated 1.2 Mg m-3 1.5 Mg m-3 of total carbon emissions in the Caobas and 20 de Noviembre ejidos, with 5% and 12% corresponding to collateral damage during felling, respectively.  Overall lower committed emissions and collateral damage from felling and skidding were present in Caobas, the FSC certified ejido. We discuss how forest certification, through implementation of reduced impact logging (RIL) practices can significantly reduce carbon emissions from selective logging in the region.